(untitled) (Revista Electrónica REDINE, 2025)
The objective of this essay is to identify the areas of employment for graduates in human development. To this end, I rely on three main sources: 1. The document Degree in Human Development: Feasibility Study and Curriculum Design; 2. My knowledge, acquired through my role on the program’s leadership team, of the general areas of employment for these graduates; and 3. The areas of employment expressed by the graduates participating in the 18th anniversary celebration. As a final reflection, I argue that: The Degree in Human Development is a versatile program, that adapts to various scenarios in working life; this versatility is possible thanks to the multidisciplinary nature of its curriculum, among other factors, such as the graduates’ own agency. As a result of this versatility, I identify the following areas of work: social responsibility, protection of vulnerable children, gender, human management, public administration, human security, human rights, human migration, among others; and that these areas occupy the three sectors: civil society (NGOs), the public sector, and the private sector.